Relapsing granulomatosis with polyangiitis provoked by trauma: A case report. Issue 3 (January 2019) - Deng, Shan; Xing, Yida; Wang, Hongjiang; Kong, Xiaodan
Abstract: Rationale: The precise cause of granulomatosis with polyangiitis (GPA) remains unclear. Herein we present a case of refractory GPA occurring after trauma. Patient concerns: A 43-year-old man suffered fractures of the left orbital in an accident, and then received surgical repair. At a postoperative follow-up, he developed maxillary sinusitis. Seven months later, he was hospitalized with symptoms of cough, high-grade fever, and loss of weight. Diagnosis: He was diagnosed with GPA based on the symptoms of upper and lower respiratory tract involvement, granulomas in a lung biopsy specimen, and presence of PR3-ANCA. Interventions: Initially the patient responded well to the treatment of glucocorticoids and cyclophosphamide (CYC). Forty days later, he was hospitalized again with symptoms of fever, cephalgia, and recurrent ulcerated subcutaneous nodules, due to the vasculitic manifestations of GPA. This time he was treated with cyclophosphamide and glucocorticoids with no improvement, and then switched to rituximab. Outcomes: After 4 doses of rituximab, the symptom of cephalgia disappeared and subcutaneous ulcerations and conjunctival congestion diminished. Lessons: Trauma may act as an inflammatory stimulus to affect the course of disease in GPA. The combination of glucocorticoids and cyclophosphamide is the standard therapy for GPA. Nevertheless, patients who have no response to CYC, especially with predominantly vasculitic manifestations, could resort to rituximab.